Nonlinear spatial impacts of the digital economy on urban ecological welfare performance: evidence from China - Wang, Sen; Li, Jinye (Frontiers in Ecology and Evolution, 2024)
With the rapid development of digital technology and its deep integration with the environmental and ecological fields, the digital economy has become an effective way to guide the transition of cities to an eco-friendly model. However, empirical studies on the nonlinear spatial effects between digital economy and ecological welfare performance are still insufficient. Methods: Based on the panel data of 270 prefecture-level cities in China from 2011 to 2020, this paper empirically examines the impact of the digital economy on the ecological welfare performance of cities and its mechanism of action using spatial econometric modeling.The promotion effect of digital economy development on the ecological welfare performance of cities is characterized by the "J" shape of increasing marginal effect, and the spatial spillover effect on the ecological welfare performance of neighboring cities is inverted U shape of inhibiting first and then promoting later. The mechanism test shows that the development of digital economy can enhance the ecological welfare performance of cities through the marginal incremental promotion of green technological innovation in local and neighboring cities and has a positive spatial spillover effect. The development of digital economy can have a direct effect of "U" shape on local ecological welfare performance by influencing factor allocation efficiency and energy utilization efficiency. It also has an inverted U-shaped spatial spillover effect. Environmental regulation has an "inverted U"-shaped moderating effect on the local eco-welfare performance affected by the digital economy. As the level of rural revitalization increases, the level of rural revitalization produces a "U" shape moderating effect of inhibiting. Heterogeneity analysis finds that digital economy development has a more significant facilitating effect and positive spatial spillover effect on the ecological welfare performance of cities in central China. Discussion: This paper will provide a reference for the synergistic optimization of digital economy development and ecological welfare performance among regions. The findings of the study will promote the development of digital economy and accelerate the realization of the goal of "Beautiful China".